Dinitreno pentaradicals: organic sextet molecules†. (3rd August 2016) - Mieres‐Pérez, Joel; Henkel, Stefan; Mendez‐Vega, Enrique; Schleif, Tim; Lohmiller, Thomas; Savitsky, Anton; Sander, Wolfram; Abe, Manabu; Sheridan, Robert S.
Abstract : A new sextet ground state molecule, the 2, 4, 6‐trichloro‐1, 3‐dinitrenophenoxyl radical, was obtained upon UVphotolysis of the corresponding diazido precursor in argon at 5 K. The sextet molecule is formed stepwise with the triplet nitrene, the quartet nitreno radical, and the quintet dinitrene as intermediates that were detected by EPR spectroscopy. IR and UV–Vis measurements only allowed us to observe the main product, the quintet dinitrene. The coupling between the two nitrene centers and the oxygen centered radical in the sextet state results in zero‐field splitting (zfs) parameters of |D/hc| = 0.088 cm −1 and |E/hc| = 0.009 cm −1, considerably larger than in previously reported organic sextet molecules. An analogous sextet dinitrene formed by replacing the oxygen centered radical by a carbon centered radical was also studied by EPR spectroscopy, and in this case the zfs parameters |D/hc| = 0.125 cm −1 and |E/hc| = 0.023 cm −1 indicate even larger spin localization. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A new sextet ground state molecule (2 ) was obtained upon UV photolysis of the corresponding diazido precursor in argon at 5°K. The coupling between the two nitrene centers and the oxygen‐centered radical in the sextet state yields zfs parameters considerably larger than in previously reported organic sextets. The analogous sextet dinitrene (1 ) was also studied by electron paramagnetic resonance spectroscopy. These sextet species could be used as new building blocks for the synthesis of organic magnetic materials.